EFFICIENCY OF TRAMP FLEET OPERATING UNDER THE CONTRACTS OF AFFREIGHTMENT - Yuliia KOSKINA; Svitlana ONYSHENKO; Oleksii DROZHZHYN; Oleksii MELNYK (Scientific Journal of Silesian University of Technology. Series Transport)
The paper considers the vessels operating on carriages of bulk cargoes to get the maximum profit for the shipowner as his main goal. The items in search are the long-term contracts of affreightment with some clauses indicated as indeterminate values, that can be described using a range of values. It leads to a range of voyage indicators. The vessels’ deployment for getting the maximum profit depends on the market situation that is to say possible changes in vessels' time-charter rates and freight rates. This paper presents the mathematical model, based on the fleet and volumes of carriages under a set of contracts of affreightment during the due time. It includes the necessity for the commitment fulfilment by owned and time-chartered vessels and takes into account possible changes in freight rates for cargoes carriages. The presented numerical example demonstrates the opportunity for practical implementation of the model.